PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (Team Games Tournament) DENGAN TIPE STAD (Student Teams Achievement Division) TERHADAP HASIL BELAJAR PASING BAWAH BOLA VOLI - rindy anggara (Program Studi Pendidikan Jasmani Universitas Negeri Jakarta, 2020)
The purpose of this study is to determine the comparison of cooperative learning models with learning outcomes under volleyball. This study compares the TGT type cooperative learning model in the experimental class with the STAD type cooperative learning model in the control class, in this study the researcher used the experimental research method. Samples were taken by purposive sampling because it was determined by class and number of students. The results showed the average value of the TGT type pretest learning model amounted to 64.88 while the average value of the STAD learning model amounted to 63.32. The results of the posttest of the TGT type learning model with an average value of 79.08 while the average value of the STAD type learning model amounted to 70.56. From the results of the study, the pretest and posttest scores of the two learning models used showed a significant increase in learning outcomes and there were differences in learning outcomes